2014
DOI: 10.1002/pssc.201400079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of doping on the optical properties of silicon nanocrystals embedded in SiO2

Abstract: Co‐implantation, with overlapping implantation projected ranges, of Si and doping species (P, As, B) followed by a thermal annealing step is a viable route to form doped Si nanocrystals (NCs) embedded in SiO2. This presentation deals with optical characterizations of both doped and undoped Si‐NC prepared by this method. The NC effective presence in the oxide layer and their crystallinity is verified by Raman spectrometry. Photoluminescence (PL) and PL excitation measurements reveal quantum confinement effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Combining the results obtained by APT, Raman, PL and PLE analysis, the authors concluded that P impurities tend to be efficiently incorporated in the Si-NC core whereas B atoms are mainly localized at the Si-NC/SiO 2 interface (see Fig. 14, top left panel) [213,214,215].…”
Section: Matrix-embedded Nanocrystalsmentioning
confidence: 83%
See 1 more Smart Citation
“…Combining the results obtained by APT, Raman, PL and PLE analysis, the authors concluded that P impurities tend to be efficiently incorporated in the Si-NC core whereas B atoms are mainly localized at the Si-NC/SiO 2 interface (see Fig. 14, top left panel) [213,214,215].…”
Section: Matrix-embedded Nanocrystalsmentioning
confidence: 83%
“…Indeed it has been demonstrated that ion beam synthesis, which is a well known approach to grow undoped Si-NCs embedded in SiO 2 , is also an efficient technique to grow doped Si-NCs with diameters of few nanometers, if the dopants are co-implanted with Si [213,214,215]. Combining the results obtained by APT, Raman, PL and PLE analysis, the authors concluded that P impurities tend to be efficiently incorporated in the Si-NC core whereas B atoms are mainly localized at the Si-NC/SiO 2 interface (see Fig.…”
Section: Matrix-embedded Nanocrystalsmentioning
confidence: 99%